In vivo RNA-seq and infection model reveal the different infection and immune characteristics of B. pertussis strains in China - Weilun Zuo; Weilun Zuo; Chen Wei; Meiyan He; Mengyao Zhang; Jiangli Liang; Xiao Ma; Na Gao; Qin Gu; Yan Ma; Jingyan Li; Shuyuan Liu; et al. (Frontiers in Cellular and Infection Microbiology)
IntroductionVarious strains emerged in B. pertussis re-emergence, the pathogenic characteristics and mechanisms remain elusive. We aimed to explore the relationship between the in vivo transcriptome and colonization advantage of various pertussis clinical strains during the B. pertussis re-emergence.MethodsFour pertussis strains were isolated from clinically suspected cases by active surveillance. The phylogenetic relationships of clinical strains and global isolates were compared by a genome-wide SNP-based phylogenetic tree and allele genotyping. LC-MS/MS analysis and binding affinity detection allowed the identification of expression and antigenicity of pertactin. The characteristics of infection and immunity of clinical strains were compared in a BALB/c mouse aerosol challenge model. In vivo RNA-seq analysis was performed in NSG mouse model to describe the transcriptome during infection, and verified by detecting biofilm formation and paraquat tolerance.ResultsThe partial pertactin-deficient strain BP-L2 was first reported. It showed significantly enhanced tracheal colonization compared to both CS and BP-L1 strains in naive mice (P < 0.0001 vs. CS) and exhibited superior fitness over BP-L1 in immunized mice (P < 0.001). BP-L1 showed superior lung colonization (P < 0.0001) and tissue-resident memory T cell induction versus BP-L2 and CS (P < 0.001). Colonization dominance of BP-L1 in lungs and BP-L2 in trachea aligned with the pathological injury (P < 0.05) and the inflammatory cytokine enhancement (IL-6 in lungs of BP-L1 group, P < 0.01). In vivo RNA-seq results revealed that BP-L2 significantly upregulated relA (log2FC = 2.1, FDR P-value = 0.019) and sodA (log2FC =2.4, FDR P-value = 8.61E-06) compared to BP-L1, functionally linked to enhanced stringent response and oxidative stress defense. BP-L1 exhibited significant in vivo bipA upregulation over BP-L2 (log2FC = 1.8, FDR P-value = 0.027) without concurrent biofilm enhancement (P = 0.51 vs. BP-L2). Furthermore, the BP-L2 and BP-L3 strains of the same ptxP1-ptxA1-fhaB3 lineage showed significantly higher paraquat tolerance than other strains (P < 0.001), showing extremely high SODs activity.ConclusionThe emerging pertussis strains exhibit different colonization advantages in the trachea or lungs, which will influence the transmission patterns of the clinical strains. The tracheal colonization advantage of the partial pertactin-deficient strain may be associated with the overexpression of the relA and sodA in vivo infection.